The Development Challenge of Finding Durable Solutions for Refugees and Internally Displaced People - Harild, Niels; Christensen, Asger (World Bank, Washington, DC, 2017)
This note discusses the development challenge of finding durable solutions for refugees and Internally Displaced Peoples (IDPs), and the relevance of this challenge for the World Development Report (WDR) on securing development in fragile and conflict affected settings. The note will describe (i) the scale, trends, and impact of forced displacement; (ii) the development challenge of finding durable solutions for those displaced; (iii) current practice on addressing this development challenge; (iv) the connections between the political, security and developmental aspects of forced displacement including regional spillover and impacts; and (v) suggestions as to what governments and the international development community can do in order to move beyond humanitarian emergency assistance and contribute to durable solutions for refugees and IDPs in return or displacement situations.